2021
DOI: 10.1101/2021.02.24.432632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A general role for MIA3/TANGO1 in secretory pathway organization and function

Abstract: Complex machinery is required to drive secretory cargo export from the endoplasmic reticulum. In vertebrates, this includes transport and Golgi organization protein 1 (TANGO1), encoded by the Mia3 gene. Here, using genome engineering of human cells light microscopy, secretion assays, and proteomics, we show loss of Mia3/TANGO1 results in formation of numerous vesicles and a loss of early secretory pathway integrity. This restricts secretion not only of large proteins like procollagens but of all types of secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…TANGO1's facilitating role in formation of large COPII vesicles is unequivocal (McCaughey et al, 2021a;Saito et al, 2009), yet there are reports of its ambiguous mechanism in the generation of large COPII vesicles. Schekman and colleagues suggest a co-packaging of TANGO1 with the cargo (Yuan et al, 2018), whereas Malhotra and colleagues demonstrated that TANGO1 does not leave the ER, but forms a ring around the COPII vesicle (Raote et al, 2018).…”
Section: Trafficking Of Mucin-2 In Enlarged Copii Vesicles Is Reminis...mentioning
confidence: 99%
See 1 more Smart Citation
“…TANGO1's facilitating role in formation of large COPII vesicles is unequivocal (McCaughey et al, 2021a;Saito et al, 2009), yet there are reports of its ambiguous mechanism in the generation of large COPII vesicles. Schekman and colleagues suggest a co-packaging of TANGO1 with the cargo (Yuan et al, 2018), whereas Malhotra and colleagues demonstrated that TANGO1 does not leave the ER, but forms a ring around the COPII vesicle (Raote et al, 2018).…”
Section: Trafficking Of Mucin-2 In Enlarged Copii Vesicles Is Reminis...mentioning
confidence: 99%
“…Overexpressing TANGO and KLHL12 confirmed their promoting role for mucin-2 trafficking as has been observed for PC1 (28), collagen IV (74) and apoB (73) trafficking, through the mono-ubiquitylation of SEC31. TANGO1's facilitating role in formation of large COPII vesicles is unequivocal (31,75), yet there are reports of its ambiguous mechanism in the generation of large COPII vesicles. Schekman and colleagues suggest a co-packaging of TANGO1 with the cargo (29), whereas Malhotra and colleagues demonstrated that TANGO1 does not leave the ER, but forms a ring around the COPII vesicle (33).…”
Section: Trafficking Of Mucin-2 In Enlarged Copii Vesicles Is Reminis...mentioning
confidence: 99%